2023
DOI: 10.1007/978-3-031-26419-1_1
|View full text |Cite
|
Sign up to set email alerts
|

LCDB 1.0: An Extensive Learning Curves Database for Classification Tasks

Abstract: The use of learning curves for decision making in supervised machine learning is standard practice, yet understanding of their behavior is rather limited. To facilitate a deepening of our knowledge, we introduce the Learning Curve Database (LCDB), which contains empirical learning curves of 20 classification algorithms on 246 datasets. One of the LCDB's unique strength is that it contains all (probabilistic) predictions, which allows for building learning curves of arbitrary metrics. Moreover, it unifies the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Though we are, in principle, willing to believe this, what proof do we really have? If anything, some recent study by Mohr et al (2022), on a large number of data sets in combination with various classifiers, showed that nonmonotonic learning curve behavior does occur. The least any practitioner should be is aware that nonmonotonicity can happen.…”
Section: Discussionmentioning
confidence: 99%
“…Though we are, in principle, willing to believe this, what proof do we really have? If anything, some recent study by Mohr et al (2022), on a large number of data sets in combination with various classifiers, showed that nonmonotonic learning curve behavior does occur. The least any practitioner should be is aware that nonmonotonicity can happen.…”
Section: Discussionmentioning
confidence: 99%
“…For this, we utilize learning curves for each of the algorithms. 54 First, the union of internal and external data was split uniformly at random, using 90% of the chemicals for training and 10% for testing. We then identified all species for which at least 128 training assays were available (with the goal to form reasonably long useful learning curves).…”
Section: ■ Experimentsmentioning
confidence: 99%